Opinion of nursing technicians on the health care policy for men - Rosineide Santana de Brito; Danyelle Leonette Araújo dos Santos; Nathaly Ellen Maria Silva Ferreira (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769210721 Objective: to identify the opinion of the nursing technicians working in the Family Health Strategy about the Brazilian Comprehensive Health Care Policy for Men. Method: an exploratory and descriptive quantitative study was conducted with 21 nursing technicians working at four Basic Health Units, in the city of Natal/RN, Brazil. Data were collected in January/February 2013, by means of forms which focused on sociodemographic variables and related to the object of study. The data analysis was carried out using descriptive statistics. This study was approved by the Research Ethics Committee of the Federal University of Rio Grande do Norte, CAAE 0114.0.051.000-11. Results: some respondents have shown lack of knowledge on the policies for men's health. However, the whole sample positioned themselves favorably to its existence and justified it by the preventive and educational character of the policy. Conclusion: it was highlighted that it is necessary for the policy to be better disseminated among professionals of health teams, in order to contribute to the improvement of men's health care.